2019
DOI: 10.1364/oe.27.028832
|View full text |Cite
|
Sign up to set email alerts
|

Parameter-based imaging from passive multispectral polarimetric measurements

Abstract: A modified pBRDF model with a diffuse scattering component is applied to estimate the complex refractive index, slope variance roughness, and diffuse scattering coefficients of object surfaces from time sequences of polarimetric images. The approach is used for the first time to produce parameter-based images from multispectral Stokes imagery of outdoor target scenes collected by the Ground Multiangle Spectro-Polarimetric Imager. The images of the estimated surface parameters show distinctions between differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“… 11 , 12 It has been previously established that light polarization is extremely sensitive to the micro-architecture and optical parameters of a variety of studied media. This property has been extensively explored in a range of contexts including remote sensing, 13 15 optical metrology, 16 18 and biomedical diagnostics. 19 21 Our previous studies clearly demonstrated that simple (i.e., circularly) polarized light is able to distinguish different grades of cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 It has been previously established that light polarization is extremely sensitive to the micro-architecture and optical parameters of a variety of studied media. This property has been extensively explored in a range of contexts including remote sensing, 13 15 optical metrology, 16 18 and biomedical diagnostics. 19 21 Our previous studies clearly demonstrated that simple (i.e., circularly) polarized light is able to distinguish different grades of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Polarization imaging technology has been applied in numerous fields, including remote sensing [2], medical diagnoses [3], defogging [4], underwater imaging [5], facial recognition [6], and target detection [7]. For the field of target detection, previous studies have shown that polarization imaging technology can improve the contrast between the artificial target and the natural background [8] [9] [10] [11] [12], and suppress cluttered signals from nature background [13], due to the material properties and surface roughness of artificial targets are different from those of natural backgrounds [14].…”
Section: Introductionmentioning
confidence: 99%